PERAN MODEL PROBLEM BASED LEARNING DALAM MENDORONG KETERAMPILAN BERPIKIR KRITIS SISWA PADA PELAJARAN IPAS SEKOLAH DASAR - Yanti Aprianti Kartini; Rahayu Victoria Solihah; Arif Maulana; Galih Dani Septiyan Rahayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the effectiveness of the Problem Based Learning (PBL)model in improving critical thinking skills of fifth grade students in Natural andSocial Sciences (IPAS) learning at SDN Sumbersari, Kabupaten Purwakarta, inthe 2024/2025 academic year. Classroom action research used StringersLook–Think–Act cycle for two cycles with 30 students. The observation instrumentwas developed based on five groups of critical thinking indicators, including simpleexplanations, basic support, inferences, advanced explanations, and strategiesand tactics. The results showed an increase in the average critical thinking scorefrom 76.40 in Cycle I to 84.95 in Cycle II (an increase of 8.55 points). All indicatorsincreased, confirming that PBL provides an authentic problem-solving context thatstimulates reasoning, reflection, and metacognitive awareness. These findingsrecommend the wider application of PBL to foster higher-order thinking skills inelementary schools.